Promoting Digital Literacy: Assessing Teachers Readiness in Utilizing Information and Communication Technology for Learning in Rural Area - Rofiah, Nurul Hidayati; Restiana, Restiana; Dewi, Rahmatika (Jurnal Prima Edukasia, 2024)
This research aims to evaluate and ascertain the readiness of teachers to utilize Information and Communication Technology (ICT) in educational settings, with a particular focus on rural environments. By examining teachers' preparedness in employing ICT, the study sheds light on the unique conditions and phenomena associated with technology use in learning activities in rural areas. The methodology adopted for this research was a descriptive qualitative approach, using a case study design focused on the island of Belitung. The study involved 12 classroom teachers from three elementary schools in Badau Village as research subjects. Data were gathered through interviews and document analysis, employing thematic analysis techniques for data interpretation. To ensure the validity of the data, techniques of technical and source triangulation were used. The findings indicate six themes regarding the teachers' readiness to use ICT, including teachers' proficiency in operating laptops/computers, and their capability to plan, select, and integrate ICT tools for educational and administrative purposes. Additionally, skills in collaboration, using the internet, and leveraging other advanced applications are deemed crucial. The study also reveals that teachers need to comprehend their roles and functions in adapting to ICT developments, thereby aligning their readiness with the standards of professional teacher competency. The study highlights the need for teachers to understand their roles in ICT adaptation, aligning with professional competency standards. These insights provide a framework for future research, policymaking, and practice enhancement in educational ICT, aiming to improve educational quality and effectiveness in the digital age.